Pengaruh Strategi Pengembangan Layanan dan Kualitas Produk terhadap Daya Saing Mie Njerit Kedai Mak Neng di Labang Madura - Nadhifa Ismiil Harokah; Jimmy Ignatius; Ageng Pratiwi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Competition in the culinary industry requires MSMEs to continuously improve their business performance to survive and excel in the market. This study aims to analyze the influence of service development strategy and product quality, both partially and simultaneously, on the competitiveness of Mie Njerit Kedai Mak Neng in Labang Madura. The research method used a quantitative approach with a survey design. The population in this study consisted of all consumers whose exact number was unknown (unknown population). A sample of 75 respondents was selected using a non-probability sampling technique with an accidental sampling method. Primary data collection was conducted through questionnaires based on a Likert scale. The t-test results indicated that the service development strategy had a positive and significant partial effect on competitiveness. Product quality also showed a positive and significant partial effect on competitiveness, emerging as the most dominant factor in this study. Furthermore, the F-test results proved that the service development strategy and product quality simultaneously had a significant effect on competitiveness. The R Square value indicated that these two independent variables were able to explain the variation in competitiveness, while the remaining percentage was explained by other variables outside this research model.